MXene based nanocomposites for recent solar energy technologies - Alhamada, T. F; M. A., Azmah Hanim; Jung, D. W.; R., Saidur; A., Nuraini; Wan Hasan, W. Z. (MDPI AG, 2022)
This article discusses the design and preparation of a modified MXene-based nanocomposite for increasing the power conversion efficiency and long-term stability of perovskite solar cells. The MXene family of materials among 2D nanomaterials has shown considerable promise in enhancing solar cell performance because of their remarkable surface-enhanced characteristics. Firstly, there are a variety of approaches to making MXene-reinforced composites, from solution mixing to powder metallurgy. In addition, their outstanding features, including high electrical conductivity, Young’s modulus, and distinctive shape, make them very advantageous for composite synthesis. In contrast, its excellent chemical stability, electronic conductivity, tunable band gaps, and ion intercalation make it a promising contender for various applications. Photovoltaic devices, which turn sunlight into electricity, are an exciting new area of research for sustainable power. Based on an analysis of recent articles, the hydro-thermal method has been widely used for synthesizing MXene-based nano-composites because of the easiness of fabrication and low cost. Finally, we identify new perspectives for adjusting the performance of MXene for various nanocomposites by controlling the composition of the two-dimensional transition metal MXene phase.